Pengaruh Minat dan Kecerdasan Emosional Terhadap Prestasi Belajar Matematika Siswa SMP - Aulia Alzak; Rustam Rustam (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2015)
The influence of interest and emotional Intelligence on mathematical learning achievement of grade VIII student of SMP Negeri 1 Latambaga can be concluded that: (1) The interest of grade VIII student of SMP Negeri 1 Latambaga is moderate, there are 31 students or 64,58% with the lowest score is 55, the higest score is 87 and the average is 71,90. (2) the emotional intelligence of grade VIII student of SMP Negeri 1 Latambaga is moderate. There are 15 students or 31,25% with the lowest score is 57, the lowest score is 95, and the average is 76,90. (3) the mathematical learning achievement of grade VIII student of SMP Negeri 1 Latambaga is moderate. There are 16 students or 33,33%, the lowest score is 75, the highest score is 88, and the average is 81,46. (4) there is not significant positive influence between interest and emotional intellegence of student towards mathematical learning achievement of grade VIII student of SMP Negeri 1 Latambaga. Where the test of hypothes is testing results indicate that thitung = 1,98 > ttabel =3,195 at significance level α = 0,05.